Special Issue - Papers from JAST Tribology Conference, Tokyo, May 2008 - Masabumi Masuko (Japanese Society of Tribologists, 2008)
The JAST Tribology Conference, Tokyo, May 2008 was held at Tokyo from Monday May 12th to Wednesday May 14th, 2008.A total of 156 presentations were made with five parallel sessions, and a total of 580 participants took part in the conference. At every Tribology Conference, JAST publishes a bound volume of proceedings, which includes extended abstracts of all the papers presented. Since the pages are limited to two pages for each paper and most of them are written in Japanese, the authors were requested to submit their paper to the JAST's official international journal “Tribology Online.”The papers submitted to the Tribology Online have subsequently undergone the normal peer review process by multiple reviewers. In this special issue, thirteen papers are published following the decision of authors themselves either not to submit their papers and the process of peer review.The Editorial Committee wishes to express their appreciation to all the authors who submitted their papers to this International Journal. As the Editor-in-Chief, I would like to express my sincere thanks to the Associate Editors, the Reviewers, and the Publication Coordinators for their effort to complete the peer-review processes and the publication work under the tight schedule.